Forecasting changes of pastries products with the use of capacitive measuring converters and current control of their structural changes - Dorohovich, Antonella; Tarasenko, Irina; Rudik, K.; Vasilenko, J. P.; Tarasenko, Sergiy (My University, 2011)
Developed new ultrastable capacitive three-pin converters for automatic control of composition and structure of food products, allowing you to monitor and predict the state of the aging of such products.Розроблені нові надстабільні ємнісні триконтактні перетворювачі для автоматичного прецизійного контролю складу та структури харчової продукції, що дозволяє контролювати та прогнозувати стан старіння такої продукції/ Разработаны новые сверхстабильные емкостные трехконтактные преобразователи для автоматического прецизионного контроля состава и структуры пищевой продукции, что позволяет контролировать и прогнозировать состояние старения такой продукции.
Keywords: microchanges parameters; parameters substances; measures capacitance; міри ємності; параметри речовин; мікрозміни параметрів; меры емкости; параметры веществ; микроизменения параметров; кафедра електропостачання і енергоменеджменту; кафедра технології хлібопекарських і кондитерських виробів